Family Child Care Providers' Compliance With State Physical Activity Regulations, Delaware Child Care Provider Survey, 2011 - Sarah Williams Leng, MA; Laura Lessard, PhD, MPH (Centers for Disease Control and Prevention, 2013)
Introduction Delaware is one state that has implemented comprehensive child care regulations to foster healthy dietary and physical activity behaviors of young children. This study describes the Delaware family child care environment and providers' knowledge of and compliance with physical activity regulations. We analyzed the data to determine characteristics associated with predictors of knowledge of and compliance with these regulations. Methods A random stratified sample of 663 licensed Delaware family child care providers was mailed a survey on family child care characteristics and providers' awareness and practices of the child care regulations. Three logistic regression models were used to explore the association between provider characteristics and their knowledge of and compliance with the regulations. Results Ultimately, 313 of the 663 eligible family child care providers participated in the survey (47.2% response rate). Controlling for covariates, we found that family child care providers' education level was significantly associated with knowledge of the physical activity regulation. Another model showed that family child care providers with larger amounts of outdoor space were more likely to report compliance with the recommendation for unstructured physical activity than those without this described space (odds ratio, 2.45). A third model showed a significant association between available indoor space for all activities including running and reported greater compliance with the recommendation for structured physical activity than was reported by caregivers with less indoor space (odds ratio, 11.2). Conclusion To provide the recommended levels of physical activity for children in child care, the available physical space environment is an important area of focus for advocates of physical activity recommendations within the family child care environment.